Prospective, randomized, double-blinded, double-dummy and multicenter phase IV clinical study comparing the efficacy and safety of PG201 (Layla) and SKI306X in patients with osteoarthritis. (2nd April 2016) - Ha, Chul-Won; Park, Yong-Beom; Min, Byung-Woo; Han, Seung-Beom; Lee, Jae Hyup; Won, Ye-Yeon; Park, Ye-Soo
Abstract: Ethnopharmacological relevance: This prospective, randomized, double-blinded, double-dummy, multicenter study compared the efficacy and safety of PG201 (Layla®), a new product from extracts of 12 plant sources and SKI306X (Joins®) which have been well investigated and in relatively wide usage among herbal medicine, for the treatment of patients with knee osteoarthritis. Aim of the study: To compare the efficacy and safety of PG201 and SKI306X in patients with knee osteoarthritis. Materials and methods: A prospective, double-blinded multicenter study was conducted in 124 patients with Kellgren and Lawrence grade 2–3 knee osteoarthritis. Patients were randomly assigned to receive 600 mg of PG201 (300 mg, twice daily) and 600 mg of SKI306X placebo (200 mg, thrice daily) or 600 mg of SKI306X (200 mg, thrice daily) and PG201 placebo (300 mg, twice daily) for 12 weeks. The primary outcome was the improvement of pain by week 8 as assessed by the 100-mm pain visual analog scale (VAS). Secondary outcomes included pain VAS improvement level at week 12, pain VAS improvement rate at weeks 8 and 12, the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) improvement level at weeks 8 and 12, the improvement of the quality of life (EQ-5D), overall symptom self-assessment score, and rescue medication consumption. Results: The pain VAS improvement at 8 weeks was 14.2±16.2 in the experimental group and 11.9±13.1 in control group (p=0.557), confirming that the experimental group was not inferior to the control group as lower limit (-8.38) of 95% CI of the difference of VAS improvement between two groups was well above the allowed limit (-10 mm). There was no significant difference in all secondary outcomes including pain VAS, WOMAC, EQ-5D, overall symptom self-assessment score, and rescue medication consumption. Adverse events were low and similar between the two groups. Conclusions: The results of this study showed that PG201 significantly reduced knee pain and improved knee function and were comparable to SKI306X. PG201 can be suggested as an effective treatment of knee osteoarthritis. Trial registration ClinicalTrials.gov:NCT01768468 Graphical abstract: The non-inferiority of the PG201 group was tested against the SKI306X group when the confirmation of two-sided 95% confidence interval(CI) showed that the lower limit of the CI was higher than the permitted limit (−10 mm).